Pattern Visual Evoked Potential Changes in Diabetic Patients without Retinopathy - Ozgur Balta; Gulten Sungur; Mehmet Yakin; Nurten Unlu; Oyku Bezen Balta; Firdevs Ornek (Journal of Ophthalmology)
Purpose. To assess the different check sizes of pattern visual evoked potential (PVEP) in diabetic patients without retinopathy according to HbA1c levels and diabetes duration. Methods. Fifty-eight eligible patients with type 2 diabetes mellitus and 26 age- and sex-matched healthy controls were included in the study. Only the right eye of each patient was analyzed. All of the patients underwent a comprehensive ophthalmic examination, and the PVEPs were recorded. Results. There was a statistically significant difference in P100 latency in 1-degree check size and in N135 latency in 2-degree check size between controls and patient groups which have different HbA1c levels. There were statistically significant, positive, and weak correlations with diabetes duration and P100 latency in 7-minute and 15-minute check sizes and N135 latency in 15-minute check size. Conclusions. It was showed that there were prolongations in P100 latency only in 1-degree check size and in N135 only in 2-degree check size in diabetic patients without retinopathy. There was statistically significant correlation between diabetes duration and P100 and N135 latencies in different check sizes.